Mimicking the immunosuppressive impact of fibroblasts in a 3D multicellular spheroid model - Grotz, Melanie; van Gijzel, Lieke; Bitsch, Peter; Carrara, Stefania C.; Kolmar, Harald; Garg, Sakshi (Frontiers in Drug Discovery, 2024)
Targeting the tumor microenvironment (TME) is an attractive strategy for cancer therapy, as tumor cells in vivo are surrounded by many different influential cell types, with complex interactions strongly affecting tumor progression and therapeutic outcome. Cancer-associated fibroblasts (CAFs) represent an abundant stromal cell type in the TME that modulate tumor development by exerting an immunosuppressive effect to influence effector immune cell activation. One promising target for TME-directed therapy is the CAF marker fibroblast activation protein-α (FAP). In this study, we employ a multicellular three-dimensional (3D) spheroid model, including tumor cells, fibroblast cells, and naïve T cells and could observe a protective effect of fibroblasts on tumor cells. Subsequently, we demonstrate that fibroblasts express FAP at differing expression levels in two-dimensional (2D) versus 3D cells. Lastly, we show that in a triple-culture of tumor cells, T cells and fibroblasts, the simultaneous assembly of fibroblasts using the high-affinity ligand oncoFAP with an engineered α-CD3-scFv-Fc-dextran-oncoFAP construct resulted in effective T cell activation to augment immunogenicity. Overall, this model can be routinely used for preclinical screening to study the effects of fibroblasts on the TME in vitro.